A Dynamic, General Equilibrium Analysis of Deviations From the Laws of One Price - Beverly J. Lapham (Queen's University, Department of Economics, 1990)
There are at least two versions of the Law of One Price under the assumptions of perfect competition, no trade barriers, and no transport costs. One version predicts equal prices of competing goods sold in the same country and manufactured by producers located in different countries. Another version predicts equal prices of a good manufactured by a single producer and sold in different countries when prices are converted to a common currency. Empirical studies suggest persistent, time-varying deviations from both versions of the Law of One Price. This paper explores a stochastic, dynamic, general equilibrium theoretical economy with explicitly strategic price setting behavior. The equilibrium processes generated by the economy exhibit properties which are generally consistent with persistent, time-varying deviations from the Laws of One Price.
Keywords: 330